Recursive Terms in Semantic Programming - Goncharov, S. S.; Sviridenko, D. I. (Siberian mathematical journal, 2018)
For constructing an enrichment of a language with restricted quantifiers, we extend the notion of term by the construction of the terms conditional and recursive with respect to lists. We show that the so-obtained extension of the language of formulas with restricted quantifiers over structures with hereditary finite lists is a conservative enrichment and the new terms are Δ-definable in the basic language.